REVITALISASI PERILAKU DAN PRESPEKTIF MASYARAKAT MELALUI PENANGANAN, PENCEGAHAN DAN EDUKASI COVID-19 - Waladdin Panggabean; Annanda Muhammad Adnan; Cholifah Aliyani; Devvy Berliana Thalitha; Diva Afifah Hakim (Wadah Inovasi Indonesia, 2022)
In the implementation of the Community service (KKN) this period is still in the period of being hit by COVID-19, which the World Health Organization (WHO) has officially declared the Corona COVID-19 virus as a pandemic. This KKN activity was carried out in Sepinggan Baru Village and focused on RT 27. From the observations we have made, there are various problems that exist in the community in Sepinggan Baru Village that need to be handled and improved. The problem is more centered on preventing COVID-19. Public awareness of safety and health is still considered lacking, the distribution of Social Assistance for the Independent Isolation community from the village in several RTs is not evenly distributed, there are no banners/appeals related to Covid-19 and an appeal for isoman for people infected with Covid-19, Houses In the house on Rt.27, especially those who carry out isomanism, the disinfectant spraying process has never been carried out, which can minimize the possibility of exposure to the Corona Virus.